Isobaric tags for relative and absolute quantification‐based proteomic analysis of Puccinellia tenuiflora inoculated with arbuscular mycorrhizal fungi reveal stress response mechanisms in alkali‐degraded soil. (30th June 2019) - Wang, Yingnan; Lin, Jixiang; Huang, Shouchen; Zhang, Liang; Zhao, Wenna; Yang, Chunxue
Abstract: Alkali soil is a major abiotic constraint that limits plant distribution and yield in the northeast of China. Puccinellia tenuiflora is considered the most promising grass species for salt‐alkali grassland restoration. However, there is little information on the molecular mechanisms underlying how arbuscular mycorrhizal fungi (AMF) enhances P. tenuiflora stress responses in alkali‐degraded soil. In this study, AMF colonization, growth, photosynthetic pigments, and inorganic ion contents were measured. Isobaric tags for relative and absolute quantification‐based quantitative proteomic technology were employed to identify the differentially abundant proteins in P. tenuiflora seedlings with or without AMF under alkalinity stress. The results showed that AMF colonization increased seedling biomass, photosynthetic pigment contents, and K + /Na + ratio under alkalinity stress. Moreover, a total of 598 proteins were significantly differentially regulated in P. tenuiflora seedlings after AMF inoculation under alkalinity stress compared with under alkalinity stress alone. The results showed that AMF inoculation significantly improved protein synthesis, reactive oxygen species scavenging, and nitrogen metabolism to promote the biosynthesis of osmotic substances in response to alkalinity stress. In addition, P. tenuiflora seedlings produced more energy to compensate for the energy loss caused by alkalinity stress after AMF inoculation. In conclusion, these findings provide new insights into the physiological mechanisms of the response to alkali‐degraded soil in P. tenuiflora seedlings with AMF and also clarify the role of AMF in the molecular regulation network of P. tenuiflora under alkalinity stress.